Reforming the financing of the European Union: A proposal - Clemens Fuest; Friedrich Heinemann; Martin Ungerer (Intereconomics, 2015)
The current system for the financing of the EU needs to be reformed. This paper puts forth a reform proposal with two important elements: first, the addition of an EU VAT share on receipts; and second, a shift in power from the European Council to the European Parliament with regard to the determination of the structure of EU expenditures. The first element will make taxpayers' contributions to the EU more visible, thereby increasing their interest in the EU budget and fostering democratic accountability. The second element will shift spending priorities away from projects that generate visible advantages to individual member states and towards policies that benefit the EU as a whole.
Keywords: 330; EU-Haushalt; Europäische Finanzpolitik; Umsatzsteuer; Öffentliche Ausgaben; EU-Staaten